2018
DOI: 10.15403/jgld.2014.1121.271.cld
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Events in Adult Celiac Disease Patients. Case Report and Review of the Literature

Abstract: Background & Aims: Celiac disease (CD) presents with a wide spectrum of extra-digestive symptoms, including hemorrhagic manifestations. The aim of this review was to conduct an extensive analysis of the hemorrhagic events reported in adult CD patients.Methods: Case report and review of the literature. Pubmed (MEDLINE) database search from January 1970 onwards was performed using the medical subject headings [MeSH] terms “celiac disease” AND “blood coagulation disorders”, “hemorrhage”, “hematoma”, “hematuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…In some cases, the electrolyte imbalances led to neurologic or cardiologic manifestations, which could be the main presenting feature in CC; a high index of suspicion is needed among physicians with regard to these atypical and very rare presentations, as they were previously shown to have poor awareness in regard to CD non-intestinal features[19]. In addition, CC can also present with bleeding diathesis, which was the case for 4/42 of the reviewed cases; as previously reported, hemorrhagic events in CD patients encompass a wide range of clinical manifestations, such as gastrointestinal bleeding, hemoptysis, epistaxis, hematuria, hematomas or ecchymosis[20].…”
Section: Discussionmentioning
confidence: 92%
“…In some cases, the electrolyte imbalances led to neurologic or cardiologic manifestations, which could be the main presenting feature in CC; a high index of suspicion is needed among physicians with regard to these atypical and very rare presentations, as they were previously shown to have poor awareness in regard to CD non-intestinal features[19]. In addition, CC can also present with bleeding diathesis, which was the case for 4/42 of the reviewed cases; as previously reported, hemorrhagic events in CD patients encompass a wide range of clinical manifestations, such as gastrointestinal bleeding, hemoptysis, epistaxis, hematuria, hematomas or ecchymosis[20].…”
Section: Discussionmentioning
confidence: 92%
“…Hemorrhagic events can be the presenting feature of CD, including cases of celiac crisis with profound malabsorption and coagulation deficits [44]. A recent review of the literature has found only case reports of hemorrhagic events, comprising otorhinolaryngology, digestive, urology, muscular and alveolar bleeding (the latter defining the Lane Hamilton syndrome) [45]. The mechanism behind hemorrhagic diathesis in CD is mainly represented by vitamin K deficiency, while some studies have also theorized mimicry between factor XIII and tissue transglutaminase [45,46].…”
Section: Hemorrhagic and Thrombotic Eventsmentioning
confidence: 99%
“…A recent review of the literature has found only case reports of hemorrhagic events, comprising otorhinolaryngology, digestive, urology, muscular and alveolar bleeding (the latter defining the Lane Hamilton syndrome) [45]. The mechanism behind hemorrhagic diathesis in CD is mainly represented by vitamin K deficiency, while some studies have also theorized mimicry between factor XIII and tissue transglutaminase [45,46]. Management of hemorrhage consists of intravenous vitamin K and GFD, along with specific measures according to bleeding site.…”
Section: Hemorrhagic and Thrombotic Eventsmentioning
confidence: 99%
“…Of children with IPH, estimates from available literature suggest that up to 30% have CD, with 75% of LHS patients presenting in childhood. 19…”
Section: Discussionmentioning
confidence: 99%